2017
DOI: 10.1016/j.ctrv.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase (PI3K) pathway inhibitors in solid tumors: From laboratory to patients

Abstract: The phosphoinositide 3-kinase (PI3K) pathway is an intracellular signaling pathway that has regulatory roles in cell survival, proliferation, and differentiation, and a critical role in tumorigenesis. In cancer, multiple studies have investigated the therapeutic targeting of the PI3K pathway, and multiple inhibitors targeting PI3K and its isoforms, protein kinase B/AKT, mammalian target of rapamycin (mTOR), and other pathway proteins have been developed. For the treatment of solid tumors, only allosteric mTOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
144
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(150 citation statements)
references
References 98 publications
3
144
0
3
Order By: Relevance
“…However, the promising clinical activity observed with buparlisib (despite only a 1.9‐month median duration of exposure to buparlisib in BELLE‐2) suggests there could be a place for PI3K inhibitors in the treatment of ABC if their associated toxicity could be reduced. Currently, isoform‐selective PI3K inhibitors are under clinical development and may offer efficacy benefits while avoiding some off‐target toxicities seen with pan‐PI3K inhibitors .…”
Section: Methodsmentioning
confidence: 99%
“…However, the promising clinical activity observed with buparlisib (despite only a 1.9‐month median duration of exposure to buparlisib in BELLE‐2) suggests there could be a place for PI3K inhibitors in the treatment of ABC if their associated toxicity could be reduced. Currently, isoform‐selective PI3K inhibitors are under clinical development and may offer efficacy benefits while avoiding some off‐target toxicities seen with pan‐PI3K inhibitors .…”
Section: Methodsmentioning
confidence: 99%
“…The PI3K/Akt pathway plays an important role in many cellular processes, such as cell survival, proliferation, migration, differentiation, and tumorigenesis [39][40][41]. Several studies have indicated that aberrant activation of the PI3K/Akt pathway is found in many human cancers, including colorectal cancer [20,42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both liphagal and siphonodictyal B have been reported to exert inhibitory activity against phosphatidylinositol 3‐kinase (PI3K), a lipid kinase that converts phosphatidylinositol 4,5‐bisphosphate to phosphatidylinositol 3,4,5‐triphosphate (PIP3). PIP3 in turn activates protein kinase B (AKT) and downstream molecules, leading to the promotion of cell growth, proliferation, and survival . In many types of cancer cells, the PI3K‐AKT pathway is frequently activated through gain‐of‐function mutations in PIK3CA, which encodes p110 α , the catalytic subunit of PI3K .…”
Section: Introductionmentioning
confidence: 99%
“…PIP3 in turn activates protein kinase B (AKT) and downstream molecules, leading to the promotion of cell growth, proliferation, and survival. 7 In many types of cancer cells, the PI3K-AKT pathway is frequently activated through gain-of-function mutations in PIK3CA, which encodes p110α, the catalytic subunit of PI3K. 8 Therefore, PI3K is considered a potential drug target for cancer therapy.…”
mentioning
confidence: 99%